2007
DOI: 10.1007/s11120-007-9281-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of highly purified prolamellar bodies reveals their significance in chloroplast development

Abstract: The prolamellar body (PLB) proteome of dark-grown wheat leaves was characterized. PLBs are formed not only in etioplasts but also in chloroplasts in young developing leaves during the night, yet their function is not fully understood. Highly purified PLBs were prepared from 7-day-old dark-grown leaves and identified by their spectral properties as revealed by low-temperature fluorescence spectroscopy. The PLB preparation had no contamination of extra-plastidal proteins, and only two envelope proteins were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 76 publications
7
75
0
1
Order By: Relevance
“…Although our study deals with the chloroplasts of an angiosperm, which differ from the chloroplasts of algae, it can be speculated that, during the thylakoid biogenesis of the angiosperm chloroplast, PLBs with connected PTs and the pyrenoid of the algae chloroplast can play a similar structural role (Rast et al, 2015). Regularity of PLBs in the bean plastids (Figure 1) was observed simultaneously with the band at 653 nm corresponding to the Pchlide-LPOR-NADPH complex ( Figure 9A) (Abdelkader et al, 2007;Blomqvist et al, 2008;Schoefs and Franck, 2008;Adam et al, 2011, and references therein). The transformation of PLBs observed after 1 h of illumination was seen as a loss of regular connections through interconnecting tubules (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although our study deals with the chloroplasts of an angiosperm, which differ from the chloroplasts of algae, it can be speculated that, during the thylakoid biogenesis of the angiosperm chloroplast, PLBs with connected PTs and the pyrenoid of the algae chloroplast can play a similar structural role (Rast et al, 2015). Regularity of PLBs in the bean plastids (Figure 1) was observed simultaneously with the band at 653 nm corresponding to the Pchlide-LPOR-NADPH complex ( Figure 9A) (Abdelkader et al, 2007;Blomqvist et al, 2008;Schoefs and Franck, 2008;Adam et al, 2011, and references therein). The transformation of PLBs observed after 1 h of illumination was seen as a loss of regular connections through interconnecting tubules (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
“…We have demonstrated that the paracrystalline structure of the PLB transforms directly to lamellar structures that are porous from the beginning. This direct transformation can explain the presence of so many photosynthetic proteins in the PLB in the darkness, which results in photomorphogenic growth upon illumination (Blomqvist et al, 2008). Already at the beginning of the untangling of the paracrystalline network, tubules were transformed into porous flat slats even in the midst of the degrading PLB (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, etioplasts, which contain prolamellar bodies (PLBs) and perforated lamellae called prothylakoids, are converted into functional chloroplasts that possess fully mature thylakoid networks. PLBs contain many of the building blocks of the thylakoid membrane, including MGDG, the chlorophyll precursor protochlorophyllide, enzymes involved in chlorophyll and carotenoid biosynthesis, and proteins involved in photosynthetic light reactions (Lonosky et al, 2004;Kleffmann et al, 2007;Blomqvist et al, 2008;Kanervo et al, 2008). This transition is therefore quite different from the one occurring at the shoot apex (from the L2 to the leaf primordia), both in its starting point (PLBs and prothylakoidcontaining etioplasts versus thylakoid-less proplastids) and its end point (fully mature versus partially mature networks).…”
Section: Comparison With Other Models Of Thylakoid Membrane Developmentmentioning
confidence: 99%
“…Sixty-four unique proteins were identified in prolamellar bodies, catalyzing pigment synthesis and various photosynthetic reactions. One POR protein, POR A, was found to dominate the proteome of prolamellar bodies, and POR B was found for the first time in dark-grown wheat (Blomqvist et al 2008). Margareta has over 60 publications on this topic in the Web of Science.…”
mentioning
confidence: 99%